The CONSTANCES cohort: an open epidemiological laboratory - Zins Marie; Bonenfant Sébastien; Carton Matthieu; Coeuret-Pellicer Mireille; Guéguen Alice; Gourmelen Julie; Nachtigal Mélissa; Ozguler Anna; Quesnot Ariane; Ribet Céline; Rodrigues Grégory; Serrano Angel; et al. (BMC, 2010)
Abstract Background Prospective cohorts represent an essential design for epidemiological studies and allow for the study of the combined effects of lifestyle, environment, genetic predisposition, and other risk factors on a large variety of disease endpoints. The CONSTANCES cohort is intended to provide public health information and to serve as an "open epidemiologic laboratory" accessible to the epidemiologic research community. Although designed as a "general-purpose" cohort with very broad coverage, it will particularly focus on occupational and social determinants of health, and on aging. Methods/Design The CONSTANCES cohort is designed as a randomly selected representative sample of French adults aged 18-69 years at inception; 200,000 subjects will be included over a five-year period. At inclusion, the selected subjects will be invited to fill a questionnaire and to attend a Health Screening Center (HSC) for a comprehensive health examination: weight, height, blood pressure, electrocardiogram, vision, auditory, spirometry, and biological parameters; for those aged 45 years and older, a specific work-up of functional, physical, and cognitive capacities will be performed. A biobank will be set up. The follow-up includes a yearly self-administered questionnaire, and a periodic visit to an HSC. Social and work-related events and health data will be collected from the French national retirement, health and death databases. The data that will be collected include social and demographic characteristics, socioeconomic status, life events, behaviors, and occupational factors. The health data will cover a wide spectrum: self-reported health scales, reported prevalent and incident diseases, long-term chronic diseases and hospitalizations, sick-leaves, handicaps, limitations, disabilities and injuries, healthcare utilization and services provided, and causes of death. To take into account non-participation at inclusion and attrition throughout the longitudinal follow-up, a cohort of non-participants will be set up and followed through the same national databases as participants. A field-pilot was performed in 2010 in seven HSCs, which included about 3,500 subjects; it showed a satisfactory structure of the sample and a good validity of the collected data. Discussion The constitution of the full eligible sample is planned during the last trimester of 2010, and the cohort will be launched at the beginning of 2011.